2016
DOI: 10.24266/0738-2898-34.3.80
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Propagation Substrate and Rooting Hormone Products to Facilitate Asexual Propagation of Silene chalcedonica and Silene coronaria

Abstract: Many ornamentals are commercially propagated by cuttings, which is an easy and cost-effective propagation method. Silene L. is a promising genus for extensive use as a landscape ornamental due to its drought tolerance, profuse flowering, and perennial characteristic. Silene is readily cross pollinated, so to ensure genetic purity for breeding and cultivar release, an asexual cutting propagation protocol needs to be established. Adventitious rooting of cuttings of Silene chalcedonica (L.) E.H.L. Krause and Sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In this respect, In rooting Silene fabaria subsp domokina with cuttings, optimum rooting (100%) was achieved with 20.75 roots of 4.84 cm length with 1000 ppm IBA (Sarropoulou et al, 2018). In rooting Silene chalcedonica with cuttings, the highest rooting rate (54.93%) and average number of roots (4,044) were obtained from the application of 1% IBA and 0.5% NAA (Jiang et al, 2016). On the other hand, it has been compared with rooting studies on other species.…”
Section: Resultsmentioning
confidence: 91%
“…In this respect, In rooting Silene fabaria subsp domokina with cuttings, optimum rooting (100%) was achieved with 20.75 roots of 4.84 cm length with 1000 ppm IBA (Sarropoulou et al, 2018). In rooting Silene chalcedonica with cuttings, the highest rooting rate (54.93%) and average number of roots (4,044) were obtained from the application of 1% IBA and 0.5% NAA (Jiang et al, 2016). On the other hand, it has been compared with rooting studies on other species.…”
Section: Resultsmentioning
confidence: 91%
“…They concluded that the appropriate rooting substrate combined with the application of the certain auxin's concentrations promoted the rooting percentage of the cuttings. According to the results of Jiang et al (2017), who studied the asexual cutting propagation of two ornamental species Silene chalcedonica and Silene coronaria, using two different propagation substrates and three different root-promoting hormone products, the rooting success of stem cuttings was highly species related. Silene coronaria cuttings rooted readily in vermiculite without an auxin treatment whereas the rooting percentage of S. chalcedonica cuttings was improved by using an auxin and grown in vermiculite.…”
Section: Resultsmentioning
confidence: 99%
“…Propagation through cuttings is a method of producing a large amount of planting material in a short period, maintaining the genetic purity of the plants (Siqueira et al, 2020). It is often followed in the reproduction of horticultural, ornamental, and protected or endangered plant species (Baul et al, 2011;Jiang et al, 2017;Siqueira et al, 2020). Although B. tymphaea can reproduce via seeds (Kyrkas et al, 2023) since it is an endemic species, the collection of seeds from the wild could affect the size of local populations.…”
Section: Introductionmentioning
confidence: 99%
“…The temperate regions of the Northern Hemisphere are the natural habitat of species that belong to the Silene genus [2]. Silene L. is a promising genus for extensive use as a landscape ornamental due to its drought tolerance, profuse flowering and perennial characteristic [3]. Several species of Silene L., a genus of the Caryophyllaceae, have been recognized as ornamental plants suitable for rock gardens, herbaceous borders, and naturalized areas [4].…”
Section: Introductionmentioning
confidence: 99%